Association Between Hyperactivity Symptoms and Somatic Complaints: Mediating and Moderating Mechanisms in Childhood Trauma and Life Events Among Chinese Male Adolescents - Wu, Shuxian; Yang, Tingyu; He, Yuqiong; Cui, Xilong; Luo, Xuerong; Liu, Jianbo (Frontiers in Psychiatry, 2021)
Background: Attention deficit/hyperactivity disorder (ADHD) is associated with various somatic complaints. However, it is unclear whether hyperactivity symptoms are related to somatic complaints among adolescents. In the present study, we analyzed the relationship between hyperactivity symptoms and somatic complaints in Chinese male adolescents and explored the underlying moderating and mediating mechanisms. Methods: Our sample included 1596 males (age=12-16) recruited as part of an epidemiological study of child and adolescent mental disorders from April to July, 2014. Hyperactivity symptoms and somatic complaints were assessed with Achenbach’s Child Behavior Checklist (CBCL), and the Childhood Trauma Questionnaire Short Form (CTQ-SF) and Adolescent Life Events Scale (ASLEC) were used to assess exposure to childhood trauma and recent life events. Results: Adolescents with hyperactivity symptoms experienced more emotional abuse, physical abuse, and life events, and reported more somatic complaints (p＜0.05). Linear regression analysis showed that hyperactivity, total childhood trauma score, emotional abuse, sexual abuse, and ASLEC score significantly predicted somatic complaints (p＜0.05). Emotional abuse and life events mediated the relationship between hyperactivity symptoms and somatic complaints. Furthermore, childhood trauma moderated the path between hyperactivity symptoms and ASLEC in the mediation model for predicting somatic complaints (p＜0.05). Conclusions: Chinese male adolescents with hyperactivity symptoms were found to experience more somatic complaints. Childhood trauma and life events were involved in explaining the relationship between hyperactivity symptoms and somatic complaints in this population. In light of these findings, interventions to address physical complaints in ADHD should consider the impact of childhood trauma and recent life events.